Inhibiting Mitochondrial Cytochrome c Oxidase Downregulates Gene Transcription After Traumatic Brain Injury in Drosophila - Shah, Ekta J.; Hüttemann, Maik; Sanderson, Thomas H.; Gurdziel, Katherine; Ruden, Douglas M. (Frontiers in Physiology, 2021)
Traumatic brain injuries (TBI) caused by a severe impact to the head alter behavior and impair physical and cognitive function. Besides the severity, type and area of the brain affected, the outcome of TBI is also influenced by the patient's biological sex. Previous studies reporting mitochondrial dysfunction mainly focused on exponential reactive oxygen species (ROS) generation, increased mitochondrial membrane potential, and altered mitochondrial dynamics as a key player in the outcome to brain injury. In this study, we evaluated the effect of a near-infrared (NIR) light exposure on gene expression in a Drosophila TBI model. NIR interacts with cytochrome c oxidase (COX) of the electron transport chain to reduce mitochondrial membrane potential hyperpolarization, attenuate ROS generation, and apoptosis. We subjected w1118 male and female flies to TBI using a high-impact trauma (HIT) device and subsequently exposed the isolated fly brains to a COX-inhibitory wavelength of 750 nm for 2 hours. Genome-wide 3’-mRNA-sequencing of fly brains revealed that injured w1118 females exhibit greater changes in transcription compared to males at 1, 2 and 4 hours after TBI. Inhibiting COX by exposure to NIR downregulates gene expression in injured females but has minimal effect in injured males. Our results suggest that mitochondrial COX modulation with NIR alters gene expression in Drosophila following TBI and the response to injury and NIR exposure varies by biological sex.